2013
DOI: 10.4007/annals.2013.177.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Quantum groups via Hall algebras of complexes

Abstract: Abstract. We describe quantum enveloping algebras of symmetric Kac-Moody Lie algebras via a finite field Hall algebra construction involving Z 2 -graded complexes of quiver representations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
198
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(200 citation statements)
references
References 12 publications
2
198
0
Order By: Relevance
“…A lot of efforts have been paid on the progress (see [3,8,20,22]) and the most recent progress is given by Bridgeland in [1]. We hope that the main result in the present paper can provide a strong evidence for the connection between canonical bases and root categories.…”
Section: Introductionsupporting
confidence: 49%
“…A lot of efforts have been paid on the progress (see [3,8,20,22]) and the most recent progress is given by Bridgeland in [1]. We hope that the main result in the present paper can provide a strong evidence for the connection between canonical bases and root categories.…”
Section: Introductionsupporting
confidence: 49%
“…Third way was introduced by Toën in [23] who constructed the derived Ringel-Hall algebra from the derived category. Recently, Bridgeland [1] gave a more clever way to consider directly the Z 2 -graded complexes (or 2-cycle complexes as called in [13], or 2-periodic complexes as in some literature) of projective modules of an algebra with finite global dimension to construct the Ringel-Hall algebra. He showed that the full quantized enveloping algebra can be also realized by his Ringel-Hall algebra.…”
Section: Introductionmentioning
confidence: 99%
“…So one considers the localization of H tw (C m (P)) with respect to the set S (cf. [1,2]). Definition 2.6.…”
Section: Hall Algebras Given A-modules L M N We Define Extmentioning
confidence: 99%
“…Since the uniqueness of the minimal projective resolution up to isomorphism, the complex C M is well-defined up to isomorphism. By [1,2], for each r ∈ Z m , we define…”
Section: Hall Algebras Given A-modules L M N We Define Extmentioning
confidence: 99%
See 1 more Smart Citation